Predictors of Mortality in Pediatric Diabetic Ketoacidosis: The Role of Serum Lactate, Dehydration, and Admission Blood Sugar Levels - Dr Mousin Mustafa, Dr Mohd Razaq, Dr Mohammad Irfan, Dr sheikh Sabat, Dr Rajinder Singh Chib. (South Eastern European Journal of Public Health, 2025)
Background : Diabetic Ketoacidosis (DKA) is a severe complication of Type 1 Diabetes (T1D) in children, associated with significant morbidity and mortality. The mortality rate varies between <1% in developed countries and 3-13% in developing countries. Effective management of DKA necessitates accurate prognostic assessment to prevent adverse outcomes. This study investigates the role of serum lactate levels, severe dehydration, and admission blood sugar levels as predictors of mortality in pediatric DKA. Methods: This prospective observational study was conducted over one year at SMGS Hospital, Jammu. It included pediatric patients (0-17 years) diagnosed with DKA. Data were collected on demographics, clinical features including severity of dehydration and laboratory findings including admission blood sugar , blood gas and urinalysis analysis, and treatment details. Outcomes assessed were length of hospital stay, intensive care requirements, and mortality. Results: Fifty patients (50% male, median age 10.5 years) were studied. The mortality rate was 8%. Non-survivors had significantly higher mean serum lactate (7.95 mmol/L vs. 5.97 mmol/L; p=0.043) and blood sugar levels (521.5 mg/dL vs. 367.83 mg/dL; p=0.001) compared to survivors. Severe dehydration was present in 100% of non-survivors vs. 13.04% of survivors (p=0.0009). Despite these findings, multivariate regression did not identify any variable as an independent significant risk factor for mortality. Conclusion: Elevated serum lactate levels, severe dehydration, and high admission blood sugar levels are associated with increased mortality in pediatric DKA. These findings highlight the need for precise assessment and management to improve outcomes. Further research is necessary to validate these predictors and optimize DKA management strategies